Graphene/h-BN plasmon–phonon coupling and plasmon delocalization observed by infrared nano-spectroscopy. Issue 27 (19th June 2015) - Barcelos, Ingrid D.; Cadore, Alisson R.; Campos, Leonardo C.; Malachias, Angelo; Watanabe, K.; Taniguchi, T.; Maia, Francisco C. B.; Freitas, Raul; Deneke, Christoph
Abstract : We observed the coupling of graphene plasmons with different surfaces using scanning near-field optical microscopy integrated into a synchrotron beamline. Abstract : We observed the coupling of graphene Dirac plasmons with different surfaces using scattering-type scanning near-field optical microscopy integrated into a mid-infrared synchrotron-based beamline. A systematic investigation of a graphene/hexagonal boron nitride (h-BN) heterostructure is carried out and compared with the well-known graphene/SiO2 heterostructure. Broadband infrared scanning near-field optical microscopy imaging is able to distinguish between the graphene/h-BN and the graphene/SiO2 heterostructure as well as differentiate between graphene stacks with different numbers of layers. Based on synchrotron infrared nanospectroscopy experiments, we observe a coupling of surface plasmons of graphene and phonon polaritons of h-BN (SPPP). An enhancement of the optical band at 817 cm −1 is observed at graphene/h-BN heterostructures as a result of hybridization between graphene plasmons and longitudinal optical phonons of h-BN. Furthermore, longitudinal optical h-BN modes are preserved on suspended graphene regions (bubbles) where the graphene sheet is tens of nanometers away from the surface while the amplitude of transverse optical h-BN modes decrease.